Effects of immersion in a simulated natural environment on stress reduction and emotional arousal: A systematic review and meta-analysis - Li, Hongyi; Ding, Yujun; Zhao, Bing; Xu, Yuhang; Wei, Wei (Frontiers in Psychology, 2023)
Abstract Background: Although the mental health benefits of exposure to simulated natural environments are well established by researchers from environmental psychology, landscape architecture, and public health, it is unclear whether and to what extent technological immersion affects these benefits. Methods: Systematical literature searches were conducted in May 2022 from six databases. The risk of bias was evaluated using the Cochrane’s Risk of Bias tool 2.0 and the Risk of Bias in Non-randomized Studies of Interventions tool. We performed a random-effects meta-regression to investigate the heterogeneity. The immersion levels of included studies were classified by projection devices and motion capture, and then subgroup analysis was conducted. Results: Twenty-six publications were included. Exposure to simulated nature was confirmed to be associated with increased positive affect 0.40 [95% confidence interval (CI): 0.22, 0.58], vigor 0.58 (95 % CI: 0.30, 0.86), calmness 0.54 (95 % CI: 0.17, 0.92) and decreased perceived stress -0.38 (95 % CI: -0.71, -0.06), total mood disturbance -0.87 (95 % CI: -1.17, -0.57), tension -0.70 (95 % CI: -0.99, -0.41), fatigue -0.60 (95 % CI: -0.91, -0.28), anxiety -0.72 (95 % CI: -1.43, -0.02), depression -0.33 (95 % CI: -0.52, -0.14), confusion -0.79 (95 % CI: -1.19, -0.40), and anger -0.54 (95 % CI: -0.76, -0.31). Gender, health status, study design, mean age, and single exposure duration were not significant when entered in a meta-regression. For positive affect, medium immersion was observed to produce a larger effect than low and high immersion. All included studies had a moderate to high risk of bias. Conclusions: Audio-visual exposure to simulated nature contributes to stress relief and emotional arousal. The immersion level explains the heterogeneity of positive affect triggered by simulated nature. Focusing on the technical features will open up new possibilities for combining actual and simulated nature's mental health benefits.